Discussion about the technical role of an engineer in ADRS - López Avilés, Carlos Antonio (2020)
This article discusses the technical role of engineering professionals in ADR (Alternative Dispute Resolution Methods). MARCs, especially in the area of contracting works whether these public or private, may require the Engineer to act, among others, as a conciliator (extrajudicial or under the FIDIC model), mediator, friendly composer, expert, adjudicator (member of a Dispute Board or dispute resolution board), or arbitrator.